2001
DOI: 10.1086/322658
|View full text |Cite
|
Sign up to set email alerts
|

A Nosocomial Outbreak of Fluoroquinolone‐ResistantStreptococcus pneumoniae

Abstract: Over the course of a 20-month period, in a hospital respiratory ward in which ciprofloxacin was often used as empirical antimicrobial therapy for lower respiratory tract infections (LRTIs), 16 patients with chronic bronchitis developed nosocomial LRTIs caused by penicillin- and ciprofloxacin-resistant Streptococcus pneumoniae (serotype 23 F). The minimum inhibitory concentration (MIC) of ciprofloxacin for all isolates from the first 9 patients was 4 microg/mL, in association with a parC mutation. Isolates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 28 publications
0
70
1
2
Order By: Relevance
“…Shefet et al in a Cochrane metaanalysis of 24 trials including 5015 randomized patients found no benefit of atypical cover (Fluoroquinolone monotherapy versus nonatypical monotherapy). Liu et al in a prospective study of 610 patients found that susceptibility of Streptococcus pneumoniae to Penicillin and azithromycin was 77.8% and 20.6% respectively, while we found sensitivity rate to penicillin and azithromycin as 18.7% and 56.2% respectively which was opposite to the findings of Liu et al [10,11,12,13] …”
Section: Discussioncontrasting
confidence: 99%
“…Shefet et al in a Cochrane metaanalysis of 24 trials including 5015 randomized patients found no benefit of atypical cover (Fluoroquinolone monotherapy versus nonatypical monotherapy). Liu et al in a prospective study of 610 patients found that susceptibility of Streptococcus pneumoniae to Penicillin and azithromycin was 77.8% and 20.6% respectively, while we found sensitivity rate to penicillin and azithromycin as 18.7% and 56.2% respectively which was opposite to the findings of Liu et al [10,11,12,13] …”
Section: Discussioncontrasting
confidence: 99%
“…18 Some evidence shows that bacterial resistance may lead to treatment failure. 19 Such uncommon reports of treatment failure with levofloxacin have occurred mostly among predisposed hospitalized patients with chronic respiratory disease. 20 In most countries, levofloxacin resistance among S pneumoniae is Ͻ1%; the minimum inhibitory concentration for 90% of isolates (MIC 90 ) remains at 1 mg/L 17 ; and, provided that optimized regimens are used, fluoroquinolones, including levofloxacin, remain highly effective against this pathogen.…”
Section: Microbiologic Considerationsmentioning
confidence: 99%
“…The emergence of quinolone-resistant S. pneumoniae (QRSP) appears to be more dependent on fluoroquinolone selection of de novo spontaneous point mutations in the quinolone resistance-determining regions (QRDRs) of the topoisomerase genes gyrA and parC than on clonal dissemination (9-13). However, some studies reported occurrences of clonal relatedness among QRSP (11,(14)(15)(16).To investigate the relative fitness of QRSP, we conducted a competition study of a fluoroquinolone-susceptible clinical strain of S. pneumoniae (EF3030) with 2 of its fluoroquinolone-resistant isogenic mutants that had 2 common QRDR point mutation combinations. These 3 strains were analyzed by using an in vitro growth model, an in vivo nasopharyngeal colonization model, and an in vivo pneumonia model.…”
mentioning
confidence: 99%
“…The emergence of quinolone-resistant S. pneumoniae (QRSP) appears to be more dependent on fluoroquinolone selection of de novo spontaneous point mutations in the quinolone resistance-determining regions (QRDRs) of the topoisomerase genes gyrA and parC than on clonal dissemination (9)(10)(11)(12)(13). However, some studies reported occurrences of clonal relatedness among QRSP (11,(14)(15)(16).…”
mentioning
confidence: 99%